In silico Identification of Ascidian-Based Lead Compound with Antibacterial Activity for Staphylococcus aureus Toxin Proteins α-Hemolysin, TSST-1 and PVL - Mohan, Naveen Kumar; Kumar, Muneeswari; Padmanaban, Amudhanila; Farhanaaz; Samad, Zakirullah; Hajamohideen, Abdul Jaffar Ali (International Journal of Pharmaceutical Investigation, 2025)
Background Antibiotic-resistant bacteria pose a significant threat to public health, leading to the development of novel therapeutic approaches. Staphylococcus aureus, a common pathogenic microbe, is a major global health problem, with 21% to 30% of humans having been exposed to microorganisms for a long time. Materials and Methods To combat this, researchers have focused on developing novel antibiotics or alternative strategies. In silico techniques, such as computer simulations and molecular modelling, have been vital in the fight against antibiotic resistance and developing improved bacterial disease treatments. Results and Discussion Structure-based virtual screening of 48 compounds from ascidians of Indian coast against the ligand-binding domain of the α-hemolysin, Toxic Shock Syndrome Toxin-1 (TSST-1) and Panton-Valentine Leukocidin (PVL) enabled to identify a lead molecule, betulin, that exhibited a favourable binding mode and docking scores greater than -7 kcal/mol. Conclusion Antibacterial activity of Betulin was also confirmed with a maximum concentration of 15 mg/mL. Further studies are needed to validate its efficacy as a treatment for bacterial infections.
Keywords: Ascidians; Molecular Docking; PVL; Staphylococcus aureus; α-hemolysin TSST-1